Analysis Of The Differences In The Use Of Zoom And Google Meet In Learning At Putra Abadi Langkat University - Sihotang, Jonhariono (Cattleya Darmaya Fortuna, 2023)
This research aims to analyze the differences in the use of Zoom and Google Meet in learning at Putra Abadi University, Langkat. Data was collected from Putra Abadi University Langkat students during 2020-2021 with a total sample of 100 students, where 50 students represented Zoom users and 50 students represented Google Meet users. With a student population of Putra Abadi University Langkat of more than 1500 people, sampling using the Slovin formula resulted in a sample size of around 316 students. The AHP method is used to analyze student perceptions of the effectiveness and importance of using Zoom and Google Meet in distance learning. The steps of AHP involve problem identification, hierarchical decomposition, pairwise comparison, and global priority synthesis. Comparisons were made using a Likert scale to assess the level of importance between elements. The results of the questionnaire given to students of the Information Systems Program at Stabat showed that only 48 students (21.43%) were interested in studying using the Zoom platform. The main reasons why students are interested in using the platform are because the lecturers use it, the image quality is better, the sound is clearer, the background replacement is easier, and the features are easier to use. There are many drawbacks to Zoom, such as the 40-minute time limit, that make it unappealing to students. On the other hand, Zoom has advantages, such as the ability to be downloaded for free with participation of up to 100 people, and the ability to schedule Zoom Live and record or save videos. The results of this research are different from the results of previous research which concluded that there was no difference in students' interest in using the Zoom Meeting and G-Meet applications. In addition, other research states that are based on student analysis, Zoom is more preferred as a learning tool than Google Meet. However, this research supports the conclusion of previous research that there are differences in student learning outcomes using G-Meet.